Synthesis and Characterization of Homo and Hetero Multi-Nuclear Complexes of Platinum Group Metals with Some New Tetrasubstituted Thioethene Derivatives - A.K. Al-Allaf, Talal; H. Buttrus, Nabeel; R. Yousif, Hikmat (Asian Journal of Chemistry, 2010)
The new tetra-substituted thioethene derivatives R2C=CR2 (R = xanthate, dithiocarbamate, dithiophosphate) react with one or mixture of two of the salts NiCl2.6H2O, Na2PdCl4 and K2PtCl4 in 1 : 2 or 1 : 4 (ligand to metal) molar ratio, respectively, to yield homo or hetero multi-nuclear complexes of the general formula MM'LCl4 and M2M'2LCl8, where M ≠ M' or M = M' = Ni, Pd, Pt. The complexes were characterized by their elemental analyses, IR and UV-vis. spectroscopy, conductivity and magnetic measurements. Conductivity data in DMSO and acetonitrile showed that some of the complexes are non-conductive assigning the formulae [MM'LCI4] or [M2M'2LCl8] and some of the them are 1 : 4 conductive assigning the formulae [MM'L]CI4 or [M2M'2LCl4]CI4. Explanations for the structural elucidation of these complexes are given and discussed.